The Influence Of Therapy Playing Cut And Stick Paper On An Anxiety In Pre-School Children Hospitalization in Blambangan Room, RSUD Prof. Dr. Soekandar Mojosari - indra yulianti (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2017)
Hospitalization is a new experience that can make the child be afraid, it can take effect for his physical and psychology because of a new environment and the officer. Afraid feels and uncertain feeling is a danger warning that can make the children take an action for the threat. As a result the child is not cooperative. Then the nurse can give the child distraction therapy with playing therapy. Playing therapy is to change the children problematic are playing with a situation. This research is to prove the influence of therapy playing cut and stick paper on an anxiety in preschool children hospitalization in Blambangan Room, RSUD Prof. Dr. Soekandar. The population is all of the preschool children, with design pre-experiment with one group pretest-posttest approach. The Sample 15 children are taken with consecutive sampling. 15 child is given playing therapy playing cut and stick paper. Collection of data taking with Spence Children’s Anxiety Scale. Then data is processed and tested by modus analysis. The anxiety score of the child before is given playing therapy is 9 (60%) normal anxiety, 5 (33,3%) slight anxiety, 1 (6,7%) medium anxiety. The anxiety score of the child after given playing therapy is 15 (100%) decreased anxiety. There was a change from before and after therapy to play cutting and sticking paper. Decreased anxiety from this stressors is delivered on the hypothalamus that will stimulate the adrenal glands to perform vasodilatation of blood vessels so that blood pressure decreases.